Intelligent Maximum Power Tracking Control For a Wind Energy System Based on Magnetic Gear Generator - Belkhir, K. S. (Engineering, Technology & Applied Science Research, 2019)
This paper studies maximum wind power extraction from magnetic gear generator using an artificial neural network for the wind energy system. High speed can be reached with this representation either with magnetic gear generator, under low wind conditions often found inland, or without mechanical gear. In order to track maximum power, the artificial neural network controller adjusts the outer rotor speed, and thus, inner rotor speed. The proposed system is supported by simulation results.